Natalya Ryabinska. Ukraine’s Post-Communist Mass Media: Between Capture and Commercialization. - Dariya Orlova (East/West: Journal of Ukrainian Studies, 2018)
Book review of Natalya Ryabinska. Ukraine’s Post-Communist Mass Media: Between Capture and Commercialization. Foreword by Marta Dyczok, ibidem-Verlag, 2017. Soviet and Post-Soviet Politics and Society 162, edited by Andreas Umland. 186 pp. Tables. Bibliography. Name Index. Subject Index. €29.90, paper.